Locus of control and technostress in Nigeria commercial banks: The nexus - Chijioke, Dibua Emmanuel; John-Akamelu, Chitom Racheal; Ejiofor, Nwanmuoh Emmanuel (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to ascertain the connection between LOC and Technostress in selected commercial banks in Nigeria. Research methodology: Survey research design was employed in this study. The study population was 400 while the sample size was 191 employees of the selected banks, arrived at through the usage of Taro Yamane formula. The instrument for data collection was a Likert Structured Questionnaire that was put through validity and reliability test. The data were analyzed with Pearson's correlation analysis, while the hypothesis was tested at 0.05 level of significance. Result: There is a significant nexus between external LOC and techno-invasion in the Banks selected (r = .942, p-value < 0.05). The increase in technological deployment and the seeming lack of control by employees lead to techno-invasion and, by extension, technostress. Limitations: The generalizability of the study was limited by not collecting data from a cross-section of respondents from the entire country. Contribution: This is a novel study in the area of LOC and technostress in Nigeria.